"On–off" switch for H2 and O2 generation from HCOOH resp. H2O2. Issue 3 (20th October 2022) - Huang, Wenkai; Xu, Fuhua; Li, Dong‐Sheng; Astruc, Didier; Liu, Xiang
Abstract: In spite of the numerous advances in the development of H2 and O2 evolutions upon water splitting, the separation of H2 from O2 still remains a severe challenge. Herein, the novel dual‐functional nanocatalysts Pd/carbon nanosphere (CNS), obtained via immobilization of ultrafine Pd nanoparticles onto CNS, are developed and employed for both selective H2 generation from HCOOH dehydrogenation and O2 evolution from H2 O2 decomposition. In these reactions, the highest activities for Pd/CNS‐800 (i.e., calcinated at 800°C) are 2478 h −1 and 993 min −1 for H2 and O2 evolution, respectively. The highly efficient and selective "on–off" switch for selective H2 generation from HCOOH is successfully realized by pH adjustment. This novel and highly efficient nanocatalyst Pd/CNS‐800 not only provides new approaches for the promising application of HCOOH and H2 O2 as economic and safe H2 and O2 carriers, respectively, for fuel cells, but also promotes the development of "on‐off" switch for on‐demand H2 evolution. Abstract : In spite of the numerous advances in the development of H2 and O2 evolutions upon water splitting, the separation of H2 from O2 still remains a severe challenge. Herein, the novel Pd/carbon nanosphere nanocatalysts are first developed and employed as efficient and dual‐functional catalysts for both selective H2 and O2 generation from HCOOH resp . H2 O2 .